Defective Carbon Nanosheets Derived from Syzygium cumini Leaves for Electrochemical Energy‐Storage. Issue 31 (16th August 2019) - Deb Nath, Narayan Chandra; Shah, Syed Shaheen; Qasem, Mohammed Ameen Ahmed; Zahir, Md. Hasan; Aziz, Md. Abdul
Abstract: We prepare defective carbon nanosheets (DCNS) that is obtained by chemical activation of Syzygium cumini leaves and employ them as electrode materials for electrochemical supercapacitors. DCNS exhibits large specific surface area ( ca . 1184.4 m 2 /g), electrical conductivity of ca. 1.23 × 10 ‐2 S/cm, moderate level of structural defects of ca . 0.72, and sufficient oxygen‐containing functional groups as well. It leads to induce huge electroactive sites, which correspond to high specific capacitance of ca. 222.26 F/g with a better durability. The low‐cost, eco‐friendly, and electroactive carbon materials could play an important role for its applications in energy‐storage devices such as batteries. Abstract : A highly porous and defective carbon nanosheet was derived from Syzygium cumini leaves and employed them as electrode materials for electrochemical charge‐storage. The presence of defects leaded to enhance the electroactive sites of ca . 1836 cm 2, which were effective to facilitate ion adsorption, ion intercalation, electrolyte diffusion at or within its pores, and redox reactions for efficient energy‐storage.